Interpretation Concept Of Tasamuh: Conflict Resolution In Multicultural Environment to Establishing Religious Moderation - Ican Mandala*; Luqyana Azmiya Putri; Helmina (Institut Agama Islam Negeri Kerinci, 2022)
Conflicts within diversity become conflicts that never stop. Even Indonesia itself also feel this. Even though this Bhineka Tunggal Ika country is seen as a country that upholds the values ​​of tolerance, various diversity lives in harmony and peace in one region. But now this nation's tolerance attitude is starting to fade and turn to intolerance by blaming each other, disbelieving each other, and not infrequently even leading to criminal acts. This conflict does not only occur between different religious communities; fellow religious communities also often occur due to differences in views. Like the conflicts that arise at the turn of the year, namely differences in views on the greeting of Merry Christmas, during the election season in Indonesia, there are always conflicts between supporters of spouses based on differences in choices. The latest phenomenon is the statement of a priest to delete several verses of the Koran. Another case is the ban on wearing the veil, cingkrang pants, and others. This conflict often occurs due to mutual self-claims as the most righteous and waning of tolerance. Even though the government always calls to implement religious moderation by respecting each other and respecting differences. It is appropriate that the tasamuh concept is re-interpreted to become a resolution of diversity conflicts. So the author unravels the concept of tasamuh in this paper by analyzing verses related to tolerance. Hopefully, this paper can help in anticipating the occurrence of diversity conflicts.